The Language Culture in English Language Learning: A Qualitative Case Study on Challenges of Students in The English Education Program at University of Nurul Jadid: The Language Culture in English Language Learning: A Qualitative Case Study on Challenges of Students in The English Education Program at University of Nurul Jadid - Adinda octavia; Moh. Sofyan Adi Pranata (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This qualitative case study explores the challenges related to language culture experienced by students in the English Education Program at the University of Nurul Jadid. By investigating students’ perceptions and experiences, the study uncovers how cultural differences between their local background and English impact their comprehension, motivation, and language use. Key challenges include difficulties in understanding cultural nuances such as idioms, social conventions, and pronunciation, alongside social stigma that hinders public English practice and confidence. Students employ strategies like code-switching, peer collaboration, and cultural mediation to navigate these obstacles. The research also highlights critical components of language culture—including linguistic and sociocultural elements—that affect learning outcomes. Findings suggest the need for culturally responsive pedagogy that integrates local cultural values and global English contexts, fostering relevance, engagement, and effective intercultural communication. This study contributes valuable insights for designing inclusive and effective English language education tailored to cultural realities in Indonesian higher education